(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The role of different environmental factors in the formation of zooplankton community in the river ecosystems of the Arpa River catchment basin was investigated. The results of the study showed that zooplankton diversity in the mentioned ecosystems was significantly affected by the river velocity, which caused not only deterioration but also improvement in the status of zooplankton diversity. It was also revealed that the main environmental factors determining the species structure of zooplankton community in the Arpa, Yeghegis and Darb rivers were oxygen saturation, total phosphorus, total suspended solids and organic matter (of terrigenous origin probably).